The Role of Notaries in Legal Protection for Consumers in Online Buying and Selling - Rahmanto, Lucius Andik (Golden Ratio of Law and Social Policy Review, 2025)
This research seeks to identify the significance of the Notary profession in safeguarding the rights of buyers engaged in online transactions and to examine the method of producing documentation that can serve as valid proof. This study represents a form of prescriptive doctrinal legal research. This study was carried out utilizing both a legal framework and a theoretical framework. The data utilized is secondary data derived from legal sources. The method employed for gathering data is by reviewing existing literature. The legal sources gathered are examined through deductive logic analysis methods. The findings from the research indicate that, at present, Notaries have no function in creating authentic deeds electronically for electronic agreements or contracts. However, Notaries can participate by issuing electronic certificates in collaboration with the Certificate Authority, serving as a reliable third party.